A Multidimensional Framework for Improving Qur’anic Teacher Performance in Formal Islamic Educational Institutions - Marlius, Farizal; Shunhaji, Akhmad; Siskandar, Siskandar; Bachrie Tanrere, Syamsul; Anwar, Chairul; Maulana, Fikri (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2025)
This study investigates the effectiveness of Qur’anic teachers in delivering instruction to learners across various age groups within formal Islamic educational institutions. The research is motivated by the absence of standardized professional criteria for Qur’anic educators, which has contributed to inconsistent teaching practices, instructional challenges, and varying interpretive outcomes among students. The study aims to (1) identify the key factors that influence Qur’anic teachers’ performance and (2) explore the strategies implemented by school leaders to enhance instructional quality. Using a qualitative design, data were gathered through interviews, classroom observations, and document analysis involving Qur’anic teachers, students, and institutional administrators. The credibility of the data was strengthened through prolonged engagement, persistent observation, and methodological triangulation. The findings indicate that effective Qur’anic teaching performance is demonstrated through strong content mastery, the application of appropriate pedagogical strategies, and the ability to address students’ inquiries using reliable scholarly sources. The study highlights the importance of clearly defined performance standards and targeted professional development initiatives in enhancing the overall quality of Qur’anic education.